1991
DOI: 10.1007/bf00164704
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH and malate-glucose ratio on the growth kinetics of Leuconostoc oenos

Abstract: Growth, substrate utilization and product formation were studied in batch cultures of a Leuconostoc oenos strain. The effect of various culture conditions, i.e. pH-control at different values and various initial concentrations of malate and glucose, on growth and metabolism were investigated. Addition of malate resulted in a marked stimulation of growth, with only a slight increase in final biomass but a high conversion yield of glucose. Under pH control this stimulation was much greater than could be accounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
2
16
0
1
Order By: Relevance
“…Salou et al. () observed that the addition of this acid to the medium resulted in faster growth of the lactic acid bacteria Leuconosto oenos up to 75 m m , whereas a slight inhibitory effect was observed above this value.…”
Section: Discussionmentioning
confidence: 99%
“…Salou et al. () observed that the addition of this acid to the medium resulted in faster growth of the lactic acid bacteria Leuconosto oenos up to 75 m m , whereas a slight inhibitory effect was observed above this value.…”
Section: Discussionmentioning
confidence: 99%
“…3 Moreover, mixotrophic conditions remain a suitable means for improving the biomass productivity of malolactic starter cultures. 3,36,37 In batch cultures of O. oeni at pH 5.0 an improved growth rate was observed when both glucose and malate were used as energy sources compared with glucose alone. 38,39 Better growth of O. oeni was obtained in the presence of sugar mixtures (glucose/fructose, glucose/sucrose and fructose/sucrose) compared with single sugars.…”
Section: Introductionmentioning
confidence: 95%
“…Yeasts Fleet, 1989;Kennes et al, 1991a;Lemaresquier, 1987;Steinkraus, 1982). (Cogan, 1987;Firme et al, 1994;Gao and Fleet, 1994;Loubiere et al, 1992;Salou et al, 1991Salou et al, , 1994Schmitt and Divies, 1991). (Cogan, 1987;Firme et al, 1994;Gao and Fleet, 1994;Loubiere et al, 1992;Salou et al, 1991Salou et al, , 1994Schmitt and Divies, 1991).…”
Section: Introductionmentioning
confidence: 99%